From nothing to everything reading and reterritorializing the song(s) “Waray-Waray” - Agustin, Efmer E. (LIRIP: Journal of Interdisciplinary Studies, 2021)
Access online through this link: https://journals.upd.edu.ph/index.php/Lirip/article/view/8820/7778